The Development of Four-tier Diagnostic Test for Identifying Misconception in Chemical Equilibrium of Students Pharmacy Vocational School - Nesiah Payung Ranggu (Educational Studies: Conference Series, 2023)
Chemical equilibrium material includes abstract concepts, mathematical calculations, and involves macroscopic, microscopic and symbolic representations. The characteristic of the chemical equilibrium have the potential to cause students to have difficulty understanding the material which can lead to misconceptions. One of the test instruments that is expected to be effective in identifying misconceptions in student is a Four-Tier Diagnostic Test. This study aimed to develope a Four-tier Diagnostic Test Instrumen that can identifity misconceptions of chemical equilibrium in student’s pharmacy vocational school, know the quality of the developed diagnostic test items and find out informations about the analysis results of the diagnostic test. This study was a development research by Borg & Gall, 4D (defining, designing, developing, disseminating) with content validation by three validators. The participants of main field testing were 60 grade XI students of pharmacy vocational school. Data collections is to provide four-tier diagnostic test in the form multiple choice with CRI (Certainty of Response Index), obeservation, interview and questionnaire. It used descriptive quantitative and qualitative. The result of is that the four-tier multiple choice diagnostic test instrument developed was declared to be feasible and met the criteria as a good problem with averege validity of 3,77 and reability of the best 0,80 included in the high category, discriminating power of the items composed 8 good questions and 12 enough questions and the difficulty test items composed 18 good questions and 2 difficult questions. There are many misconceptiond from chemical equilibrium developed. This research only developed Four-tier diagnostic test in the conigtive. The next researcher can be combine in the cognitive and afektif. Four-tier diagnostic test is able to identifity misconseptions of chemical equilibrium.